2021
DOI: 10.3889/oamjms.2021.5841
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in Health Students during Coronavirus Disease-19: Systematic Review

Abstract: Purpose: This study aims to examine the description of mental health characteristics of health students who conducted studies during the COVID-19 pandemic. Methods: The design of this study is to use a systematic review approach by collecting several articles from a database that has been selected consisting of Springer. , ScienceDirect and ProQuest with articles published in 2020. Search for articles was carried out by entering the keyword "mental health AND student AND COVID-19". The search for this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A meta-analysis reviewed 27 studies assessing the psychological effects of COVID-19 among 90,879 college students in 15 countries, and found that 39.4%, 31.2%, 26.0%, 29.8%, and 50.5% of students had anxiety, depression, stress, post-traumatic stress, and impaired sleep quality, respectively [ 18 ]. The study reported the adverse psychological effects on university or college students, and highlighted the necessity of establishing appropriate health interventions or strategies to meet their emotional and psychosocial needs [ 19 , 20 , 21 ]. Nehir and Gungor Tavsanli (2021) found a significant relationship between the fear of COVID-19 and students’ emotional states.…”
Section: Background Literaturementioning
confidence: 99%
“…A meta-analysis reviewed 27 studies assessing the psychological effects of COVID-19 among 90,879 college students in 15 countries, and found that 39.4%, 31.2%, 26.0%, 29.8%, and 50.5% of students had anxiety, depression, stress, post-traumatic stress, and impaired sleep quality, respectively [ 18 ]. The study reported the adverse psychological effects on university or college students, and highlighted the necessity of establishing appropriate health interventions or strategies to meet their emotional and psychosocial needs [ 19 , 20 , 21 ]. Nehir and Gungor Tavsanli (2021) found a significant relationship between the fear of COVID-19 and students’ emotional states.…”
Section: Background Literaturementioning
confidence: 99%
“…A study from 2009 to 2015 showed that, except for bipolar disorder, bulimia, and schizophrenia, a significantly elevated prevalence of mental disorders was observed in college students [ 14 ]. A multitude of studies has also reported alarming results of an even increased rate of mental disorders among college students during the COVID-19 pandemic [ 15 17 ]. An interview survey study found that the COVID-19 outbreak increased anxiety among college students due to health-related concerns, difficulties in concentrating, sleep disruptions, decreased social interactions, and concerns over academic performance [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The students’ mean scores of all four QOL domains (physical, psychological, social, and environmental) significantly lowered compared to WHO reference data [ 25 ] and local frontline nurses [ 26 ]. These studies highlighted the significance of early managing students’ health problems and establishing health promotion programs to improve their physical, psychosocial, and mental health and wellbeing [ 13 , 17 , 19 , 20 , 23 ]. Besides, Worsley and her team (2022) analyzed 27 various interventional review research studies conducted over the past two decades to support college and university students’ mental health and wellbeing [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, students in healthcare programs have been more predisposed to mental health problems due to heavy academic study workloads and stressful clinical practicum [12][13][14]. The hectic clinical training in hospitals initiated additional undesirable psychological and physiological influences on their wellbeing due to the pandemic [15][16][17][18][19][20][21][22][23][24]. Mulyadi et al's (2021) systematic review and meta-analysis found a high prevalence of health problems among 13,247 nursing students in 17 studies, including sleep disturbances (27%), stress (30%), anxiety (32%), fear (41%), and depression (52%) [19].…”
Section: Introductionmentioning
confidence: 99%